Improving Kraft Pulp Mill Energy Efficiency through Low-Temperature Hydrothermal Carbonization of Biological Sludge - Jussi Saari; Ekaterina Sermyagina; Katja Kuparinen; Satu Lipiäinen; Juha Kaikko; Marcelo Hamaguchi; Clara Mendoza-Martinez (Energies, 2022)
Of the various waste and side streams created in a kraft pulp mill, the biological sludges from the wastewater treatment plant are some of the most problematic to handle. Incineration is becoming a common solution as landfilling is no longer permitted by legislation in many countries, but this is also problematic due to the high moisture content, poor drying characteristics, and high ash content in the solids. This study evaluates the technical potential of mild hydrothermal carbonization (HTC) at 160 °C for 3 h to improve the energy efficiency of on-site incineration as a biosludge handling method. HTC treatment transforms wet organic substrates into a hydrophobic carbonaceous material (hydrochar). The heating value and elemental composition of both the sludge and the hydrochar product were analyzed. Based on this, a hydrothermal carbonization model developed earlier was adjusted for the feedstock, and process integration modelling performed to evaluate the performance impact on the power and heat generation at the mill. The results indicate that if the alternative is combustion in the power boiler, HTC pre-treatment could allow a significant increase in power generation. If the sludge is combusted in the recovery boiler, a practice often avoided in order to not introduce non-process elements to the chemical recovery cycle but sometimes necessary due to, e.g., absence of a power boiler, a much smaller increase is obtained. The increase is smallest if the freed evaporator plant capacity cannot be utilized for increasing the firing liquor dry solids content.